PENGARUH MEDIA GAMBAR FOTOGRAFI TERHADAP KEMAMPUAN MENULIS TEKS EKSPLANASI SISWA KELAS XI SMK PAB 3 MEDAN ESTATE - Amaluddin Amaluddin (Jurnal Akrab Juara, 2019)
This research aims to describe text writing ability explanatory text before and after using the photographic picture media and description is there the effect of photographic image media on writing ability explanatory text class students XI SMK PAB 3 Medan Estate Year Of Learning 2018/2019. Research population is a class student XI SMK PAB 3 Medan Estate Year Of Learning 2018/2019. that number 66 students. and who become research samples as much 34 students, the class XI Accounting for pre-test and post-test classes, appearance of this sample is done by using class random sampling. This research method is experimental method. Research instruments used are esay tests formed written tested before and after participating in learning using photographic image media. The conclusions obtained from this study are ability to write explanatory text before using media photographic images got pre-test 74,12 in category B (good), the ability to write explanatory text after using photographic image media got A post-test score of 84.56 in category A (very good). The use of photographic media images has a significant influence on students' ability to write explanatory text. The price of = 8.093 is greater than at = 0.05 = = 66 which is 8.093 1,668 so that the better use of photographic image media then bushkin improves the ability of students to write explanatory texts.